Color Terms of Shan Language Speakers in Ban Wiang Wai, Monpin Sub-District, Fang District, Chiangmai Province - Aroonroek, Wanwanat (Language and Linguistics, 2021)
This article aims to study the number of basic color terms and their evolution in Shan language speakers in Ban Wiang Wai, Monpin Sub-District, Fang District, Chiangmai Province according to the theory of Berlin and Kay (Berlin & Kay, 1991) and the theory of strategies for forming words in the Shan language. The data were collected from 20 Shan people whose ages ranged between 50-60. The result of this study indicated that the numbers of basic color terms in Shan comprised 11 words, namely /kha:w1/ (white) /lam1/ (black) /lɛ:ŋ1/ (red) /khe:w1/ (green) /lə:ŋ1/ (yellow) /sɔm2/ (blue) /nam5tha:n1/ (brown) /mo:ŋ5/ (purple) /khɔŋ2/ (pink) /som5/ (orange) and /taw4/ (grey). The evolution of basic color terms in the Shan language is at the 7th stage. It accords with the theory of Berlin and Kay. Regarding non-basic color terms, the Shan language has four strategies for forming non-basic color terms: by using specific color terms; combining color terms; combining color terms with modifying words; using the names of specific objects as color terms. This study found that the most used strategies for forming non-basic color terms in this sample group was “using names of the specific objects as color terms”. We argue that this is because Shan people are continually influenced by, and are accepting of, urban society, and also because they have a way of life which is close to nature.